Youth education through focus group discussions: An effective strategy for preventing early marriage and child violence - Yulianti Yulianti; Ida Widaningsih; Hajar Nur Fathur Rohmah (Science Midwifery, 2026)
Early marriage remains a problem that impacts health, psychological, social, and economic aspects, and increases the risk of violence against children. This study aims to analyze the effectiveness of educational media through the Focus Group Discussion (FGD) method in increasing adolescents' knowledge about the dangers of early marriage and the risks of violence against children. The study used a quasi-experimental design with a one-group pretest-posttest design. The study was conducted in February 2026 at SMPN 2 Cikarang Utara, Wanajaya Village, Bekasi Regency, involving 30 adolescents as a sample. Data were analyzed using the Wilcoxon test to compare the level of knowledge before and after the intervention. The research results show that the focus group discussion (FGD) method is effective in increasing adolescents' knowledge about the impacts of early marriage and the risks of violence against children. The FGD method enables adolescents to better understand the dangers of early marriage, recognize the risks of violence against children, and be better prepared to apply this information in their daily lives. The findings of this study indicate that adolescent education through Focus Group Discussions (FGDs) is effective in increasing adolescents' knowledge, awareness, and attitudes regarding the dangers of early marriage and the risks of violence against children. Therefore, the FGD method can be implemented as an effective educational strategy in schools and communities to support efforts to prevent early marriage and protect children on an ongoing basis.